New Zealand Oligocene land crisis : integrated micropaleontology of Waikato coal measures and associated sediments in central North Island, New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Earth Science at Massey University, Palmerston North, New Zealand - Shepherd, Claire Louise (Massey University, 2012)
The topic of complete inundation of the New Zealand landmass during the Oligocene is a contentious one, with some proponents arguing the possibility that Zealandia became completely submerged during this time, and others contesting the persistence of small islands. The outcome of this debate has significant implications for the way in which modern New Zealand flora and fauna have evolved. This research project addresses the topic from a geological point of view by analysing late Oligocene–early Miocene sediments in the Benneydale region, in order to establish the timing of marine transgression in this area. Samples from two cores drilled in the Mangapehi Coalfield were analysed for palynological and calcareous nannofossil content, and these data were used to determine the age and paleoenvironment of Waikato Coal Measures, Aotea Formation and Mahoenui Group. Additionally, data from 28 boreholes in the coalfield were utilized to construct a series of isopach maps to elucidate changes in the paleostructure through time. All data were combined to develop a series of paleogeographic maps illustrating the development of coal measures and associated sediments across the Benneydale region. The results of this study indicate a Waitakian (late Oligocene-early Miocene) age for Waikato Coal Measures in the Benneydale region. Although this finding is consistent with the idea that Waikato Coal Measures young to the south, it appears that deposition occurred later than previously thought. Additionally, palynological data signify the persistence of a well vegetated pollen source throughout the late Oligocene–early Miocene sequence. Isopach analysis reveals the presence of paleohighs in the eastern and southern regions of the coalfield. While there is no direct evidence of land persisting in the Benneydale region, the pollen and isopach results support the hypothesis that some land remained above sea level during the Oligocene.
Keywords: Oligocene, New Zealand; Paleontology, New Zealand; Sedimentation and deposition; Benneydale geology; Waikato coal measures; New Zealand landmass, Oligocene